The Impact of The Job Creation Law on The Open Unemployment Rate in Indonesia: A Synthetic Control Method Approach (2015–2024 - Ramadhani, Callista Aulia; Rahmawati , Farida (Jurnal Ragam Pengabdian, 2026)
This study examines the impact of Indonesia’s Job Creation Law (Law No. 11 of 2020) on labour market outcomes, with particular emphasis on the open unemployment rate. It is motivated by the ongoing debate over labour-market deregulation in Indonesia. While the reform was intended to enhance labour-market flexibility, attract investment, and expand employment opportunities, concerns remain regarding job quality and labour precarity. The study employs a quantitative quasi-experimental design using the Synthetic Control Method to estimate Indonesia’s counterfactual trajectory based on a weighted combination of Asian countries with similar pre-intervention characteristics. The pre-intervention period spans 2015 to 2020, while the post-intervention period covers 2021 to 2024. Predictor variables include GDP per capita, inflation, foreign direct investment net inflows, trade openness, and urban population. The findings show that Indonesia’s post-intervention unemployment trajectory generally lies below its synthetic counterpart, with an average gap of approximately -0.700 percentage points. These results suggest a relative improvement in open unemployment following the policy’s implementation, although placebo tests provide only moderate inferential support. The study concludes that the law is associated with lower open unemployment, while underscoring the need to monitor job quality, informality, and the longer-term sustainability of labour-market change.